SUBSEQUENT MYOCARDIAL INFARCTION: RISK ASSESSMENT AND PREVENTION - I. V. Samorodskaya; S. A. Boytsov (Российский кардиологический журнал, 2017)
The article is focused on the reasons for lack of a precise data and issues related to population assessment of morbidity/mortality in subsequent myocardial infarctions (re-MI). Significant factors for re-MI development are age older than 60 y., comorbidities, treatments. The evaluation and significance of re-MI risk factors do influence the specifics of database formulation, parameters selection for analysis. The reasons underscored, that lead to secondary prevention of cardiovascular events, but not second infarction itself. Briefly the approaches to secondary prevention listed.